Parias, squares, queens: the other in Fábio Carvalho’s films - Barbosa, Paulo Roberto de Carvalho (Farol, 2024)
This article examines the role of the other in selected films by filmmaker Fábio Carvalho. In the light of philosophical studies on otherness, as well as interviews with Fábio Carvalho, the text deals with the way urban characters are shown by shorts made by the director in the 1990s. These are marginal figures from Belo Horizonte city, captured in the context they live, in a time when films like these were very rare. The shorts point to the singularity of the characters, who reinvent themselves in the urban scenery, showing their multiple and changing faces, despite of the invisibility with which they are seem.